An Investigation of Green Product Innovation on Consumer Repurchase Intention: The Mediating Role of Green Customer Value - SAPUTRA, Murry Harmawan; KRISTYASSARI, Bening; FARIDA, Naili; ARDYAN, Elia (Journal of Environmental Management and Tourism; Vol 11 No 3 (2020): JEMT Volume XI Issue 3(43) Summer 2020DO - 10.14505//jemt.11.3(43).16, 2020)
This study examines the critical role of green customer value in order to increase purchase intention based on green products. Data analysis techniques were carried out using Structural Equation Modeling with Partial Least Square (SEM-PLS). The respondents used in this study were the low-cost green car (LCGC) users in Central Java, Indonesia. The number of samples used was 240, with a purposive sampling technique. The findings of this study indicate that all hypotheses are supported. Green customer value is also proven to mediate (partial mediation) the relationship between green product innovation and repurchase intention. This explains that environmentally friendly product innovation by companies will be able to increase consumer buying interest if green customer value can be proven to be encouraged. The results also show that the consumer repurchase intention is influenced by consumer attitudes towards green brands and the quality perceived by consumers in the green products they use. This finding contributes theoretically and practically.